Integrating Electronics and Microfluidics on Paper. Issue 25 (2nd May 2016) - Hamedi, Mahiar M.; Ainla, Alar; Güder, Firat; Christodouleas, Dionysios C.; Fernández‐Abedul, M. Teresa; Whitesides, George M.
Abstract : Paper microfluidics and printed electronics have developed independently, and are incompatible in many aspects. Monolithic integration of microfluidics and electronics on paper is demonstrated. This integration makes it possible to print 2D and 3D fluidic, electrofluidic, and electrical components on paper, and to fabricate devices using them.